Tư tưởng Hồ Chí Minh về gia đình và ý nghĩa của nó đối với xây dựng gia đình văn hóa ở Việt Nam hiện nay : Luận văn ThS. Triết học: 60 22 03 01 - Nguyễn, Thị Yến (ĐHKHXH&NV, 2017)
93 tr. + CD-ROM + Tóm tắt